2021
DOI: 10.3390/agriculture11010066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cellulase and Lactic Acid Bacteria Inoculant to Modify Ensiling Characteristics and In Vitro Digestibility of Sweet Corn Stover and Cassava Pulp Silage

Abstract: Improving the productive performance of agricultural residue silage has practical relevance to sustaining livestock production. Sweet corn stover (SCS) and cassava pulp (CSVP) are widespread in the tropics as low-cost feed resources. To efficiently prepare SCS and CSVP silage, the impact of adding Acremonium cellulase (AC), Lactobacillus casei strain TH14 inoculant (TH14), and their combination (AC+TH14) on ensiling characteristics, microbial population, chemical compositions, and in vitro digestibility were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
4
19
1
Order By: Relevance
“…The reduction of NDF and ADF contents with AC is associated with enzymatic saccharification, releasing fermentable sugars for lactic acid fermentation. The slight delignification of TH14 in GMSH crop silage was consistent with a previous study on cassava pulp silage [41]. Probably, the TH14 strain stimulated the growth of other fiber-decomposing microbes that result in a reduction in fibrous contents and delignification [41].…”
Section: Characteristics Of Chemical Compositions In Gmsh Crop Silagesupporting
confidence: 89%
See 3 more Smart Citations
“…The reduction of NDF and ADF contents with AC is associated with enzymatic saccharification, releasing fermentable sugars for lactic acid fermentation. The slight delignification of TH14 in GMSH crop silage was consistent with a previous study on cassava pulp silage [41]. Probably, the TH14 strain stimulated the growth of other fiber-decomposing microbes that result in a reduction in fibrous contents and delignification [41].…”
Section: Characteristics Of Chemical Compositions In Gmsh Crop Silagesupporting
confidence: 89%
“…The slight delignification of TH14 in GMSH crop silage was consistent with a previous study on cassava pulp silage [41]. Probably, the TH14 strain stimulated the growth of other fiber-decomposing microbes that result in a reduction in fibrous contents and delignification [41].…”
Section: Characteristics Of Chemical Compositions In Gmsh Crop Silagesupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it is necessary to add other microbes that are able to break down lignins during the production of silage. Moreover, Kaewpila et al (2021) found that cellulases or T. harzianum attractive inoculates enhanced the ensiling features of maize silage. In addition, lactic acid production increased when a mixture of enzyme extract and L. bulgaricus was added (Table 3), which demonstrated that the combined enzyme and L. bulgaricus treatment may be more effective compared to the enzyme extract treatment alone; these results were in agreement with a previous study by Li et al (2018).…”
Section: Enzyme Productionmentioning
confidence: 99%